Normative Disharmony in Notary Summoning Procedures: Analyzing the Conflict Between Law No. 2 of 2014 on the Position of Notary and the 2025 Criminal Procedure Code - Michael Josef Widijatmoko; Lisza Nurchayatie (Jurnal Legisci, 2025)
The enactment of Indonesia's 2025 Criminal Procedure Code (KUHAP 2025) has created a critical normative conflict with Law No. 2 of 2014 on the Position of Notary (UUJN), specifically regarding procedures for summoning notaries and seizing their deeds. While the UUJN mandates prior approval from the Notary Honorary Council (MKN) as a procedural safeguard, KUHAP 2025 introduces emergency seizure provisions that potentially bypass this requirement, undermining legal certainty and professional integrity. This article aims to analyze this normative disharmony, assess its impact on fundamental legal principles, and propose a harmonization model. Employing a normative legal research methodology, the study finds that the conflict erodes legal certainty, justice, legal protection, and transparency, placing notaries in an untenable "double bind." It concludes that a comprehensive reconstruction—encompassing legislative amendments to reinforce lex specialis, institutional collaboration, and technological modernization of evidence handling—is imperative. The implication is that such multi-dimensional solutions are essential to reconcile effective law enforcement with the protective safeguards necessary for the notarial profession and the rule of law in Indonesia.